2001
DOI: 10.1128/iai.69.12.7234-7241.2001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 6-Hydroxydopamine on Host Resistance againstListeria monocytogenesInfection

Abstract: Recent studies have shown that immunocompetent cells bear receptors of neuropeptides and neurotransmitters and that these ligands play roles in the immune response. In this study, the role of the sympathetic nervous system in host resistance against Listeria monocytogenes infection was investigated in mice pretreated with 6-hydroxydopamine (6-OHDA), which destroys sympathetic nerve termini. The norepinephrine contents of the plasma and spleens were significantly lower in 6-OHDA-treated mice than in vehicle-tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 51 publications
4
24
0
Order By: Relevance
“…Ablation of the SNS prior to gram-negative bacteria challenge, such as Listeria monocytogenes, Pseudomonas aeruginosa or Escherichia coli, reduces bacterial dissemination [299][300][301][302]. This SNS effect is mediated via increased secretion of peritoneal TNF, phagocytic activity, and influx of monocytes into the peritoneal cavity [302].…”
Section: Sympathetic Activation and Endotoxic Shock: Inflammatory Andmentioning
confidence: 99%
“…Ablation of the SNS prior to gram-negative bacteria challenge, such as Listeria monocytogenes, Pseudomonas aeruginosa or Escherichia coli, reduces bacterial dissemination [299][300][301][302]. This SNS effect is mediated via increased secretion of peritoneal TNF, phagocytic activity, and influx of monocytes into the peritoneal cavity [302].…”
Section: Sympathetic Activation and Endotoxic Shock: Inflammatory Andmentioning
confidence: 99%
“…In particular, catecholamines induce elevation in the number of circulating lymphocytes both in humans (4) and mice (5). The global effect of b-agonists on immunity was mainly studied by chemically depleting natural catecholamine stocks using 6-hydroxydopamine, which results in increased innate immune responses against bacteria (6), increased adaptive immune responses against virus (7), and decreased immune responses against Gram-positive bacteria (7)(8)(9). Additionally, surgical removal of the ocular sympathetic nerve affects the generation and maintenance of immune privilege in the eye (10).…”
mentioning
confidence: 99%
“…On the other hand, in rat models that are resistant to amoebiasis it is known that immune response eliminate the most of the amebic load at the first 24 h, with high recruitment of neutrophils in acute phase, and lately with increment of macrophages (Pérez-Tamayo et al;Tsutsumi et al, 1990). Miura et al (2001) demonstrated that chemical sympathectomy with 6-OHDA improves survival in mice infected with Listeria monocytogenes, with augmented production of IFN-g, IL-1b, IL-2, IL-4 and IL-6; conversely, noradrenaline inhibited their secretion, but no change was observed in IL-4. Moreover, sympathetic denervation impacted T cells activity by reduction of reactivity in mice before sensitization with trinitrophenil hapten (Madden et al, 1989).…”
Section: Discussionmentioning
confidence: 99%